ABSURDITY IN PUTU WIJAYA’S SHORT PLAY - Sathotho, Surya Farid (Institut Seni Indonesia Yogyakarta, 2021)
Short play known as Drama Pendek (Drapen) is the latest form of Putu Wijaya's work. The play only ranges from two to twelve pages. From the number of pages, it is assumed that the drapen performance will only last five to ten minutes. Although only a short duration, Putu Wijaya is consistent with the aesthetic concept of terror. This concept, if traced further, is a derivative of the concept of the theater of the absurd. To see the possibility of performing the drapen, an analysis of the structure and texture of randomly selected drapes will be carried out. The analysis is carried out with a theoretical approach that sees the terror in the structure and texture in a drafted text. It is hoped that the results will show whether the short play meets the rules of dramaturgy to be performed on stage Key words: Short play, Theater of the Absurd, Putu Wijaya